MANGGUA - Aziz Azhari; Wimbrayardi Wimbrayardi; Esy Maestro (FBS Universitas Negeri Padang, 2014)
Abstract The cultural phenomenon of extracting the essence of sugar palms at Simalanggang Limapuluh Kota could not be separated from daily life of socienty at Simalanggang. The phenomenon referred to astructural sistem wich reflected the people’s way of thinking since it was created and developed by people themselves. This cultural was actually created in order to fulfill their needs. The cultural phenomenon was then tranferred into an idea of makin komposition about how people conducted the cultural of extracting the essence of sugar palm. However, it was not the process extracting that was tranferred. It was values of togetherness, considerateness, cooperation, and appreciation that were described into sounds. Fundamentally, it was assumed that traditional and western music colud ideally elaborate the values within the cultural phenomeonon. Kata Kunci : Air niro, Kebudayaan, Toleransi, Gotong Royong